Stock Prices and the Supply of Information - Brennan, Michael J.; Hughes, Patricia J. (Journal of Finance, 1991)
We develop a model in which the dependence of the brokerage commission rate on share price provides an incentive for brokers to produce research reports on firms with low share prices. Stock splits therefore affect the attention paid to a firm by investment analysts. Managers with favorable private information about their firms have an incentive to split their firm's shares in order to reveal the information to investors. We find empirical evidence that is consistent with the major new prediction of the model, that the number of analysts following a firm is inversely related to its share price.